Effects of Dietary Taurine Supplementation to Gilts during Late Gestation and Lactation on Offspring Growth and Oxidative Stress - Xu, Mengmeng (Animals (Basel), 2019)
SIMPLE SUMMARY: Previous studies showed that gilts had elevated oxidative stress during late gestation and lactation, and could affect offspring growth. Taurine (Tau) is an important regulator of oxidative stress and possesses growth-enhancing properties. Our results suggested that taurine supplementation during late gestation and lactation of gilts increased growth performance in piglets through improved milk quality of gilts and intestinal morphology and barrier function of offspring. ABSTRACT: Birth is one of the most important events of animal production agriculture, as newborns are abruptly forced to adapt to environmental and nutritional disruptions that can lead to oxidative damage and delay in growth. Taurine (Tau) is an important regulator of oxidative stress and possesses growth-enhancing properties. In the present study, we investigated the effects of dietary Tau supplementation in gilts during late gestation and lactation on the growth performance of piglets by assessing intestinal morphology and barrier function, and oxidative stress status. Sixteen gilts were randomly allocated to the Con (basal diet) and Tau (basal diet with 1% Tau) groups from 75 d of gestation to weaning. Maternal dietary Tau supplementation significantly increased weaning weight and average daily gain weight in piglets. Piglets in the Tau group had higher villus height and villus height-to-crypt depth ratio (VCR), ZO-1 protein expression, and secretory immunoglobulin A (sIgA) content in the jejunum. Meanwhile, Tau bebeficial affected the milk quality of gilts, as indicated by decreased malondialdehyde (MDA) concentration and increased total superoxide dismutase (T-SOD), total antioxidative capability (T-AOC), glutathione peroxidase (GPx), and catalase (CAT) activity. Furthermore, Tau supplementation increased T-SOD activity in plasma and SOD2 protein expression in the jejunum in the piglets. In conclusion, this study provides evidence that dietary Tau supplementation to gilts improves growth performance in piglets, owing to improved intestinal morphology and barrier function, as well as inhibition of oxidative stress.